(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the opinions of professors and students in the health field at a university regarding Integrative and Complementary Practices (ICPs). Methodology: A questionnaire was administered to assess the epidemiology, knowledge, and opinions on the effectiveness, relevance, and applicability of ICPs. Results: The majority had prior contact with ICPs (p<0.01). 82.8% consider ICPs effective and agree on their use in hospitals (p<0.01). 84.09% would recommend ICPs to their patients in practice. Participants agreed that teaching ICPs is essential in health-related degree programs (p<0.01), yet they do not believe the university provides effective training for professional practice (p<0.01). Conclusion: Overall, participants reacted positively to ICPs, considering them effective and relevant for use in hospitals, and expressed the need for a curriculum dedicated to ICPs during undergraduate education. However, the current situation reveals a low number of universities adopting ICP education, resulting in a workforce ill-prepared to implement ICPs in practice. Therefore, there is a clear necessity for these practices within the academic setting to foster a more humanized and interdisciplinary approach to patient care.